Comparative performance analysis of software-defined networking vs conventional IP networks using IGP protocols - Nicolas Viuche, Santiago; Paola Estupiñán Cuesta, Edith; Carlos Martínez Quintero, Juan (Bulletin of Electrical Engineering and Informatics, 2025)
The exponential growth of users in data networks presents significant challenges in terms of availability and traffic management. The advent of software-defined networking (SDN) technology offers new opportunities for enhancing performance and reducing operational costs. This article compares traditional data networks using conventional routing protocols like OSPF with SDN networks. An evaluation scenario was designed to assess the performance of conventional data networks configured with OSPF against those implemented with SDN using OpenFlow. Performance tests were conducted with various packet sizes, evaluating round-trip time (RTT) and jitter metrics using GNS3 and Mininet software to simulate conventional and SDN networks, respectively. The results demonstrated superior performance in SDN, with shorter transmission times; RTT values reached a maximum of 0.18 ms for packets ranging from 32 to 512 bytes, and jitter values remained below 1 ms. Furthermore, a routing analysis highlighted the need for specifying path redundancy in SDN environments via simulation scripts, a limitation not observed in conventional networks. This emphasizes the importance of addressing this issue when deploying SDN in production environments.